Manajemen Laba pada Periode Initial Public Offering dan Dampaknya pada Persistensi Laba - Halim, Hansen; Pangestu, Stevanus (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p16, 2020)
The paper examinse whether Indonesian corporations manage their earnings through real activities and accrual accounting during their initial public offerings. We also investigate the effect of this IPO earnings management on earnings persistence in the subsequent period. Seventy-three non-financial IPOs during 2014-2017 were taken as research sample. Afer a series of statistical analyses, we find that companies that went public committed both real and accrual earnings management to inflate income figures in their IPO year. Furthermore, we also find that accrual earnings management negatively affects earning persistence, whereas real earnings management positively affects earnings persistence. Keywords: IPO; Earnings Management; Earnings Persistence, Go Public.